1554 An Educational Programme Focusing on Paediatric Fracture Identification Maintains a Low False-Negative Radiograph Initial Report Rate in Emergency Medicine. (October 2012) - Fox, T; Rowland, A
Abstract : Introduction: False negative radiograph reports constitute greater than 80% of all diagnostic errors in Emergency Departments (EDs) with reported levels of false negative initial reports around 1%. Method: The records of all patients recalled to the Emergency Department clinics for management of a possible false-negative initial radiograph report were examined (n=46), following which the junior emergency medicine doctors received three tutorials on fracture identification and management. A re-audit was completed. Results: Between 1 st September 2010 and 16 th January 2010 a false negative radiograph report rate of 0.72% was identified. There were proportionally more false negatives in patients aged under 16. Between 16 th January and 31 st May 2011, after the educational intervention, the false negative radiograph report rate had dropped to 0.62%. The percentage reduction in false negative reports was 13.8% (p=0.53). Conclusions: These results suggest that a well developed educational programme is an effective way of maintaining a low level of false negative initial reports in an Emergency Department. False negative reports were most likely in fractures of the foot, wrist, elbow and those in the paediatric population. Educational sessions should focus on identification of these fractures. Mistakes in diagnosis can occur when an inexperienced clinician dismisses a positive clinical examination after mis-interpreting an imaging investigation. Encouraging senior review of paediatric radiographs could help to maintain a low false-negative report rate. This study indicates that educational interventions may have the potential to improve patient care in the Emergency Department setting. Further ways to reduce human error need to be explored.